A Method of Determining the C/N Ratio from Aerobically Treated Brem Compost Waste - Kindriari Nurma Wahyusi; Nur Aini Fauziyah (Department of Chemistry, Faculty of Science and Technology UIN Maulana Malik Ibrahim Malan, 2022)
The preparation of compost from brem waste has been carried out with the aim of utilizing brem waste into more useful materials. In this work, brem waste was collected from UD.Tongkat Mas, Madiun, East Java. Brem waste compost was processed by aerobic method by adding eggshell powder and M-Bio activator. The M-Bio activator solution that was added was varied with the volume of the solution, i.e., 50, 75, 100, 125 and 150ml. Here, we gave the sample nomenclature of CM50, CM75, CM100, CM125, and CM150, respectively, with the numbers on the back side indicating the volume of M-Bio activator added. Observations on brem compost were carried out for 10 days. Every 2 days interval, measurements of the C/N ratio were carried out on the compost. The manufacture of compost has been successfully made (based on SNI Standard 19-7030-2004) and has the best results by adding 100 ml of M-Bio activator (CM100) with a composting time of 10 days, with a C/N ratio of 11.42, and has no odor.